Optimum frequency and pitch range - Sheela Kumar (Journal of All India Institute of Speech and Hearing, 1970)
'Most of the therapies of voice disorders are based on the belief that a person has an optimum pitch at which the voice will be of good quality and will have a maximum intensity with the least expense of energy and they concern themselves mainly with altering the habitual pitch level or making the case to use his optimum pitch' (N. P. Nataraj 1972).